Okay, here we have this:
Considering the provided function, we are going to calculate the asymptotes, so we obtain the following:
Vertical asymptotes:
They correspond to the singularities of the functions or zeros of the denominator, in this case:
2x+1=0
2x=-1
x=-1/2
The vertical asymptote is x=-1/2.
Horizontal asymptotes:
Since the degree of the numerator is equal to the degree of the denominator plus 1, the asymptote is steep, and corresponds to the quotient of the polynomial division. Then:
![\begin{gathered} (6x^2+7x-9)/(2x+1) \\ =3x+(4x-9)/(2x+1) \\ =3x+2+(-11)/(2x+1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dd22ql2jfwkziv9p3fbtbtqombdv1yspl0.png)
Therefore the sloped asymptote is:
y=3x+2
Graphing the function and asymptotes: